2017
DOI: 10.1080/00222895.2017.1400947
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Fine Motor Loss and Allodynia in Fibromyalgia: An fNIRS Study

Abstract: Recent studies showed that fine motor control dysfunction was observed in fibromyalgia (FM) syndrome as well as allodynia. However, brain signatures of this association still remain unclear. In this study, finger tapping task (FTT) and median nerve stimulation (MNS) were applied to both hands of 15 FM patients and healthy controls (HC) to understand this relationship. Hemodynamic activity was measured simultaneously using functional near-infrared spectroscopy (fNIRS). Experiments were analyzed separately by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Fibromyalgia patients are affected by slowness in motor initiation [28, 29]. A study on fNIRS-related finger tapping changes in FM patients confirmed reduced motor performances and reduced activation of several brain areas that showed enhanced oxygenated hemoglobin levels in controls [30]. Our study cannot resolve the question of whether the motor impairment could be a consequence or a cause of cortical motor network dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Fibromyalgia patients are affected by slowness in motor initiation [28, 29]. A study on fNIRS-related finger tapping changes in FM patients confirmed reduced motor performances and reduced activation of several brain areas that showed enhanced oxygenated hemoglobin levels in controls [30]. Our study cannot resolve the question of whether the motor impairment could be a consequence or a cause of cortical motor network dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Fourteen studies out of the 19 reported a mean pain intensity rating, either at the moment of the participation [ n = 10; ( 24 , 27 , 31 , 34 , 36 , 37 , 57 60 )] or within the last month prior [ n = 4; ( 30 , 33 , 35 , 61 )]. In nine studies, including five in the meta-analysis ( 32 , 57 , 59 , 61 , 62 ), individuals with fibromyalgia were instructed to stop taking their medication prior to their participation ( 27 , 30 , 32 , 33 , 57 , 59 , 61 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TDT was assessed with Von Frey filaments in all studies except one ( 60 ) in which unspecified nylon filaments were used. For the TPT, five studies involved pinprick stimulators ( 27 , 28 , 30 , 32 , 35 , 36 , 61 ), five involved Von Frey filaments ( 34 , 37 , 57 , 62 , 63 ), one involved unspecified nylon filaments ( 60 ) and one involved disposable needles ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Often the standardized assessment of allodynia utilizes monofilaments or exposure to light brush strokes (Maracle et al, 2017). Many of the COPCs exhibit allodynia including fibromyalgia (Eken et al, 2017), TMD (Ernberg, Hedenberg-Magnusson, Alstergren, Lundeberg, & Kopp, 1999), migraine (Tietjen et al, 2009), and chronic fatigue (Yasui et al, 2014). In general, allodynia may be a by-product of the CS concept of “mental load” (Crettaz et al, 2013).…”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnosmentioning
confidence: 99%